2017
DOI: 10.3390/nu9050513
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impact of Nutrition on Immune System Recovery from Heavy Exertion: A Metabolomics Perspective

Abstract: This review describes effective and ineffective immunonutrition support strategies for the athlete, with a focus on the benefits of carbohydrates and polyphenols as determined from metabolomics-based procedures. Athletes experience regular cycles of physiological stress accompanied by transient inflammation, oxidative stress, and immune perturbations, and there are increasing data indicating that these are sensitive to nutritional influences. The most effective nutritional countermeasures, especially when cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
116
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(120 citation statements)
references
References 91 publications
1
116
0
3
Order By: Relevance
“…In moderately active healthy individuals, 20 min of cycling at 80% maximal workload decreased plasma AA and increased AA epoxide catabolic products, but did not change AA epoxide concentrations (Giordano, Newman, Pedersen, Ramos, & Stebbins CL et al, 2011). More recently, Nieman and Mitmesser (2017) described OxL patterns in response to a 75 km time trial in trained normal weight cyclists, and Stanford et al (2018) reported OxL changes with submaximal aerobic exercise in healthy adults. Yet, no studies have addressed exercise OxL patterns by comparing metabolically unhealthy and healthy states, and there is a paucity of information regarding acute changes in eCBs with moderate exercise.…”
Section: Introductionmentioning
confidence: 99%
“…In moderately active healthy individuals, 20 min of cycling at 80% maximal workload decreased plasma AA and increased AA epoxide catabolic products, but did not change AA epoxide concentrations (Giordano, Newman, Pedersen, Ramos, & Stebbins CL et al, 2011). More recently, Nieman and Mitmesser (2017) described OxL patterns in response to a 75 km time trial in trained normal weight cyclists, and Stanford et al (2018) reported OxL changes with submaximal aerobic exercise in healthy adults. Yet, no studies have addressed exercise OxL patterns by comparing metabolically unhealthy and healthy states, and there is a paucity of information regarding acute changes in eCBs with moderate exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenol supplementation is increasingly popular in athletic populations [282]. This is founded upon moderate evidence of enhanced skeletal muscle recovery from micro-damage [283], blunted exercise-associated immunosuppression [284] and in some cases improved (1-3%) endurance exercise performance [285]. With respect to polyphenol supplementation and exercise-induced GI barrier integrity, the effect of daily quercetin supplementation (2 g•day one hour pre-exercise) on GI permeability following the first and seventh days of a standardised isothermic walking (100 min; 1.8 m•s −1 in 46…”
Section: Polyphenolsmentioning
confidence: 99%
“…Metabolomics identifies the final endpoints of biochemical processes and closely reflects an organism's phenotype, environment and behavior [2]. Exercise metabolomics can provide valuable insights regarding the end biological impact of repeat and prolonged physical activity [3] as well of the biological processes associated with higher levels of endurance performance. The metabolomic profile associated with superior endurance sports performance has yet to be explored, though metabolomics studies have already identified choline-containing compounds and certain phospholipids to be positively associated with level of physical fitness [4,5].…”
Section: Introductionmentioning
confidence: 99%